2001
DOI: 10.1021/la001694s
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, Chemical Composition, and Electrochemical Characteristics of Colored Titanium Passive Layers

Abstract: Brightly and uniformly colored passive layers on Ti are formed by application of ac polarization in aqueous NH4BF4. A wide spectrum of well-defined colors is accomplished by varying the ac voltage. The passive films are stable in the ambient and in aqueous chloride, perchlorate, and sulfate solutions. Optical microscopy and scanning electron microscopy analyses indicate that the passive layers are compact and do not show fractures or cracks. An X-ray photoelectron spectroscopy (XPS) characterization of the col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 20 publications
1
58
0
Order By: Relevance
“…Such results confirm the transparent character of the films, as well as the occurrence of iridescence. This interference phenomenon, defined as constructive light interference between the beam reflected at the outer film-air interface and the inner metal-film interface, 63,64 induces the coloration of the films because their thicknesses, as determined by SE, AFM, and profilometry, are in the order of the wavelength of visible light. 65,66 It has already been mainly observed for titanium (e.g., refs 46, 63, 64, 67-70) and stainless steel (e.g., refs [71][72][73], but is here reported for the first time for cobalt.…”
Section: Physical Aspects Of Anodized Cobalt Surfacesmentioning
confidence: 99%
“…Such results confirm the transparent character of the films, as well as the occurrence of iridescence. This interference phenomenon, defined as constructive light interference between the beam reflected at the outer film-air interface and the inner metal-film interface, 63,64 induces the coloration of the films because their thicknesses, as determined by SE, AFM, and profilometry, are in the order of the wavelength of visible light. 65,66 It has already been mainly observed for titanium (e.g., refs 46, 63, 64, 67-70) and stainless steel (e.g., refs [71][72][73], but is here reported for the first time for cobalt.…”
Section: Physical Aspects Of Anodized Cobalt Surfacesmentioning
confidence: 99%
“…Titanium oxide (TiO 2 ) nanotubes and nanostructure materials are of considerable interests for their applications in photovoltaic cell [1], photocatalysis [2], sensing [3,4], and biomedical industry [5,6] due to their unique physical and chemical properties [7][8][9]. Many approaches such as templating synthesis [10,11], hydrothermal reactions [5,12], and anodic oxidization [13][14][15][16][17] have been developed for preparing nanostructure materials.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, none of the 10 medially breached screws from this study would have been identified as such, based on screw stimulation alone [i.e., thresholds ranged between 11.8 and .30 mA, all exceeding the "accepted" upper cutoff of 6-11 mA reported by a number of previous studies (Calancie et al, 1994;Clements et al, 1996;Glassman et al, 1995;Kim et al, 2004;Lewis et al, 2001;Maguire et al, 1995;Raynor et al, 2003, Reidy et al, 2001Rodriguez-Olaverri et al, 2008;Samdani et al, 2010)]. Titanium, both alloyed and commercially pure, spontaneously forms a thin (,10 nm) native oxide when exposed to oxygen-containing media (e.g., air, blood) (Donley and Gillette, 1991;Hrapovic et al, 2001;Huang et al, 2003;Milosev et al, 2000;Scharnweber et al, 2002;Sul et al, 2001;Velten et al, 2002). Titanium, both alloyed and commercially pure, spontaneously forms a thin (,10 nm) native oxide when exposed to oxygen-containing media (e.g., air, blood) (Donley and Gillette, 1991;Hrapovic et al, 2001;Huang et al, 2003;Milosev et al, 2000;Scharnweber et al, 2002;Sul et al, 2001;Velten et al, 2002).…”
Section: Figmentioning
confidence: 90%
“…Titanium, both alloyed and commercially pure, spontaneously forms a thin (,10 nm) native oxide when exposed to oxygen-containing media (e.g., air, blood) (Donley and Gillette, 1991;Hrapovic et al, 2001;Huang et al, 2003;Milosev et al, 2000;Scharnweber et al, 2002;Sul et al, 2001;Velten et al, 2002). These increases in oxide thickness, or crystallinity, correlated with transitions in the apparent color of the implant (Hrapovic et al, 2001;Sul et al, 2001;Velten et al, 2002). These anodization treatments cause the natural oxide to thicken, gradually organizing into a crystalline structure that can become highly porous (Aladjem, 1973;Kim and Ramaswamy, 2009;Park et al, 2007;Zhu et al, 2001).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation